Pyogenic granuloma caused by afatinib: Case report and review of the literature. (25th November 2015) - Inoue, Akiha; Sawada, Yu; Nishio, Daisuke; Nakamura, Motonobu
Abstract: We report on the first case of pyogenic granulomas caused by afatinib. We also review the current literature concerning pyogenic granulomas caused by epidermal growth factor receptor tyrosine kinase inhibitors.